Reverse‐Cycle Intrinsic Finks. (14th November 2019) - Choi, Sungho
Abstract: There is an ongoing debate among metaphysicians of dispositions about whether intrinsic interferers are possible for dispositions. What is interesting about this debate is that, whilst it is widely noted that dispositional interferers can work on a 'reverse' cycle, the possibility of reverse‐cycle intrinsic interferers has been put on the sidelines with all the attention being paid to the possibility of their 'normal' cousins. Presumably this is due to the perception that a discussion of reverse‐cycle interferers will be a trivial repetition of a discussion of normal ones. But I will argue that this perception is wrong. Whilst I acknowledge that there is a significant symmetry between the possibility of normal interferers and that of reverse‐cycle ones, it is not a trivial task to give an account of intrinsic interferers in a way that accommodates this symmetry. In fact, when we examine the justifications the participants in this debate have offered for their positions, it will emerge that they are all under pressure to reject the possibility of reverse‐cycle intrinsic interferers. What is intriguing about this result is that what advocates of the possibility of normal intrinsic interferers have said in support of that possibility, rather unexpectedly, puts pressure on them to reject the possibility of reverse‐cycle intrinsic interferers. Combined with the symmetry between the possibility of normal interferers and that of reverse‐cycle ones, this will pose a serious challenge to them.